2022
DOI: 10.29329/ijpe.2022.426.2
|View full text |Cite
|
Sign up to set email alerts
|

Reading Difficulty and Development of Fluent Reading Skills: An Action Research

Osman Gedik,
Hayati Akyol

Abstract: In this study, it was aimed to remediate the reading difficulties of a fifth-grade student having no physical or mental problem but experiencing reading difficulties and to develop his skills of reading fluency. For this purpose, the repeated reading, paired reading, and word repetition techniques were used in the research process. In addition, the meaning analysis, word map and vocabulary notebook techniques were also used due to the positive effect of rich vocabulary knowledge in remediating reading difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This shows that students' reading fluency skills should be developed in the early period and reading difficulties should be eliminated. One of the most recommended strategies to overcome fluent reading difficulties is repeated reading (Gedik & Akyol, 2022;National Reading Panel, 2000;Therrien & Hughes, 2008;O'Connor et al, 2007). However, it will be more effective to use repeated reading together with other strategies and techniques, one of these other strategies is paired reading and the other is the word drill technique, which allows to correct errors during reading (Welsch, 2007).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…This shows that students' reading fluency skills should be developed in the early period and reading difficulties should be eliminated. One of the most recommended strategies to overcome fluent reading difficulties is repeated reading (Gedik & Akyol, 2022;National Reading Panel, 2000;Therrien & Hughes, 2008;O'Connor et al, 2007). However, it will be more effective to use repeated reading together with other strategies and techniques, one of these other strategies is paired reading and the other is the word drill technique, which allows to correct errors during reading (Welsch, 2007).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…One of the students revealed that she usually writes down the new words in a notebook and draws relevant images related to the words as she finds it easier to remember. This is closely linked to visual students as the student can reinforce the new words with the image representation for a long-term memory (Gedik & Akyol, 2022). There was one student who claimed that she preferred to write down the new words she learned but she prefers to make associations with other similar words like synonyms, mnemonic or even homophones.…”
Section: Rq1 -What Is the Preferred Language Learning Strategy In Lea...mentioning
confidence: 98%
“…In contrast to speaking skill, reading is considered a receptive skill in which language students only receive the language without producing it. Reading skill can be defined as the mental processes of producing meaning by subjecting texts and symbols to cognitive processes (Gedik & Akyol, 2022). Santi et al ( 2021) also described reading skill as a cognitive activity that helps readers to learn new things or expand their knowledge by comprehending the text being read.…”
Section: Reading Skillmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, if our friends say that we are lazy, then our perception of these words is only a joke. However, we will be offended if someone else says it (Gedik & Akyol, 2022). In this case, our experience can influence how we interpret a word someone else conveys to us or how people perceive us (Steel et al, 2024).…”
Section: Introductionmentioning
confidence: 99%